2021
DOI: 10.1111/jcmm.16678
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 inhibition attenuates atrial fibrosis and atrial fibrillation vulnerability induced by angiotensin‐II by reducing TGF‐β1/Smads pathway activation

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(156 reference statements)
1
6
0
Order By: Relevance
“…S5 I). Based on the sequencing results, we found significant differences in the expression of transcription factors SPI1/PU.1, which regulates TGFβ1 by enrichment analysis of the sequencing results [30] , [31] . Western blot results also further demonstrated that ANGPTL8 KO could significantly reduce SPI1 expression in the livers of mice treated with HFD for 36 weeks ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…S5 I). Based on the sequencing results, we found significant differences in the expression of transcription factors SPI1/PU.1, which regulates TGFβ1 by enrichment analysis of the sequencing results [30] , [31] . Western blot results also further demonstrated that ANGPTL8 KO could significantly reduce SPI1 expression in the livers of mice treated with HFD for 36 weeks ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Alternatively, there is also evidence to suggest that Rho (56) and Akt(57) may directly stimulate PU.1 activity. PU.1 inhibitor is available and has been tested in different models of tissue fibrosis (40,58). It would be of interest to determine whether PU.1 inhibition could alter renal fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu et al. concluded that SPI1 suppression reduces angiotensin-II-induced atrial fibrosis, indicating the potential therapeutic value of SPI1 [ 15 ]. Besides, inhibition of SPI1 distinctly reduces inflammation and fibrosis in a dietary mouse model with nonalcoholic steatohepatitis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of SPI1 reduces the expression of pro-inflammatory genes to restrict microglial inflammation [ 14 ]. A previous study suggested that SPI1 repression ameliorates angiotensin-II-induced atrial fibrosis [ 15 ]. Of note, SPI1 is a transcription factor of the E26 transformation specific family, a large family of transcription factors that contains 28 family members and takes part in various cell processes, which was reported to be associated with the co-expression of S100A9 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%